Tinjauan Aplikasi Kpi Di Unit Sp Inventory Sebagai Salah Satu Alat Penilaian Kinerja Karyawan - Dinda Aulia Rahmada (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to determine the use of the kpi application as a tool for assessing employee performance in the sp inventory unit and to find out the obstacles in using the kpi application as a tool for evaluating employee performance in the sp inventory unit. This type of research is field research or field research and is descriptive in nature. The data collection techniques used are interviews and documentation. From the results of this study the method used by PT Semen Padang is applied in each unit including the sp inventory unit, which uses the kpi application to evaluate the performance of its employees. However, the implementation of this method is still considered ineffective. This is because there are still many employees who consider formality, assessments are subjective, there are no clear and measurable standards, as well as feedback on employee performance achievements. As a result, employees feel uncomfortable and unmotivated at work. Interviews are a method of collecting data by asking questions about the use of the KPI application as a means of assessing employee performance in the SP Inventory unit. Then the collected data is analyzed using inductive thinking. The results of this study can be concluded that the use of the KPI application as a tool for assessing employee performance and the constraints in using the KPI application as a tool for assessing employee performance are internal factors and external factors.